ANALISIS PERTUMBUHAN EKONOMI DAN DAYA SAING DAERAH KABUPATEN ENDE TAHUN 2013-2014 - Syafitri Permata Putri; Estherlina Sagajoka (JURNAL EQUILIBRIUM, 2021)
This study is to empirically determine the potential economic sector, to see whether there has been a change in the economic structure and to determine which economic sectors have regional competitiveness in Ende Regency in 2013-2017 through data sourced from the Central Statistics Agency (BPS) of Ende Regency. The analysis technique used is the Location Quotient (LQ) analysis and Shift Share analysis, the results of the Location Quotient analysis show that the base sector for the 2013-2017 period is 1). Wholesale and retail trade, car and motorcycle repair (1.42); 2). Transportation and Warehousing Sector (1.28); 3). Real Estate Sector (1.17); 4) Manufacturing Industry Sector (1.14); 5). Education Service Sector (1.13); 6). Other Service Sector (1.12); 7). Waste Water Treatment and Recycling Sector (1,10); 8). Construction Sector (1.02). And the non-base sector is 1). Corporate Service Sector (0.03); 2). Food and beverage accommodation provision sector (0.49); 3). Information and communication sector (0.60); 4). Health Services and Social Activities Sector (0.82); 5). Government Administration, Defense and Compulsory Social Security Sector (0.84); 6). Agriculture, forestry and fisheries sector (0.92); 7). Electricity and Gas Procurement Sector (0.93); 8). Financial Services and Insurance Sector (0.98); and 9). Mining and Quarrying Sector (0.99). Based on the analysis of Shift Share, the sectors that have competitiveness in Ende Regency are 1). Growth of Agriculture, Forestry and Fisheries Sectors; 2). Mining and Excavation Sector; 3). Real Estate Sector; 4). Corporate Service Sector and 5). Education Service Sector.